The Genetics of Primary Haemorrhagic Stroke, Subarachnoid Haemorrhage and Ruptured Intracranial Aneurysms in Adults - Peck, George (Public Library of Science, 2008)
BACKGROUND: The genetic basis of haemorrhagic stroke has proved difficult to unravel, partly hampered by the small numbers of subjects in any single study. A meta-analysis of all candidate gene association studies of haemorrhagic stroke (including ruptured subarachnoid haemorrhage and amyloid angiopathy-related haemorrhage) was performed, allowing more reliable estimates of risk. METHODS: A systematic review and meta-analysis of all genetic studies in haemorrhagic stroke was conducted. Electronic databases were searched until and including March 2007 for any candidate gene in haemorrhagic stroke. Odds ratio (OR) and 95% confidence intervals (CI) were determined for each gene disease association using fixed and random effect models. RESULTS: Our meta-analyses included 6,359 cases and 13,805 controls derived from 55 case-control studies, which included 12 genes (13 polymorphisms). Statistically significant associations with haemorrhagic stroke were identified for those homozygous for the ACE/I allele (OR, 1.48; 95% CI, 1.20–1.83; p = 0.0003) and for the 5G allele in the SERPINE1 4G/5G polymorphism (OR, 1.42; 95% CI, 1.03–1.96; p = 0.03). In addition, both &b.epsi;2 and &b.epsi;4 alleles of APOE were significantly associated with lobar haemorrhage (OR, 1.81; 95% CI, 1.26–2.62; p = 0.002 and OR, 1.49; 95% 1.08–2.05; p = 0.01 respectively). Furthermore, a significant protective association against haemorrhagic stroke was found for the factor V Leiden mutation (OR, 0.30; 95% CI, 0.10–0.87; p = 0.03). CONCLUSION: Our data suggests a genetic contribution to some types of haemorrhagic stroke, with no overall responsible single gene but rather supporting a polygenic aetiology . However, the evidence base is smaller compared to ischaemic stroke. Importantly, for several alleles previously found to be associated with protection from ischaemic stroke, there was a trend towards an increased risk of haemorrhagic stroke.